REPRESENTATION OF WOMEN IN STONE SCULPTURAL ART AND ICONOGRAPHY OF ANCIENT KASHMIR - Paray, Abdul Adil (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Throughout its history Kashmir has experienced an art life very much its own as well as accepting and absorbing influences and imported from neighbouring areas. The sculptural masterpieces that have survived in the valley have attracted the attention of art-historians and the scholars in the allied disciplines from time to time and have always been praised for their fine workmanship and iconographic features. Sculptors have not created the images only for the religious purpose but in the images are added subtle human moods and sentiments and have captured various states of emotions and feelings. Artists have captured the rhythm of life of all living beings in general and represented women in particular on the surfaces of the temples and in images. The aesthetic aspect of the sculptural motifs of the temple and images depends upon the religious canons of measurement in art. The carving approach of Kashmir's ancient and early medieval temples Goetz (1951) and Goetz (1969) includes a significant number of female images. Women from various cultures are portrayed in sculptures. Women can be seen here in a variety of subjects. The sculptures show representations of many feminine beauty ideals. This essay aims to shed light on the representation of women in Kashmir's early sculpting and iconographic traditions.